Ischaemic heart disease – a selected review of recent developments. (November 2015) - George, Sudhakar; Calvert, Patrick A.
Abstract : Purpose of review: The purpose of this review is to highlight important and interesting advances in the field of ischaemic heart disease that have occurred over the last 18 months. It is focused on research that is likely to lead to changes in clinical practice. Recent findings: There is new evidence on appropriate pharmacotherapy during angioplasty in both stable and unstable patients. The use of pressure wire assessment has been shown to improve patient outcome. The management of patients with ST elevation myocardial infarction (STEMI) is likely to change with a reduction in the use of manual thrombectomy and an increase in the treatment of nonculprit disease. Summary: The optimal duration of dual antiplatelet therapy in percutaneous coronary intervention remains an intensely debated topic with contradictory results from major trials. Pressure wire guided coronary intervention reduces the need for urgent revascularization. The use of fractional flow reserve computed tomography has the potential to revolutionize functional testing. The treatment of patients presenting with ST elevation myocardial infarction is likely to change dramatically. Heparin with bailout glycoprotein IIbIIIa-inhibitor (GPIIbIIIa-I) appears superior to bivalirudin alone, although there is no longer a role for routine manual thrombectomy. Multivessel PCI to establish complete revascularization may become the gold standard in patients presenting with STEMI, although larger trials are needed. Novel therapies are being devised for the treatment of patients with intractable angina, but further work is required in this area.